2020
DOI: 10.1021/jacs.9b12800
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Predicting Post H-Atom Abstraction Selectivity through Reactive Mode Composition Factor Analysis

Abstract: The selective functionalization of C–H bonds is one of the Grails of synthetic chemistry. In this work, we demonstrate that the selectivity toward fast hydroxylation or radical diffusion (known as the OH-rebound and dissociation mechanisms) following H-atom abstraction (HAA) from a substrate C–H bond by high-valent iron-oxo oxidants is already encoded in the HAA step when the post-HAA barriers are much lower than the preceding one. By applying the reactive mode composition factor (RMCF) analysis, which quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 81 publications
7
39
0
Order By: Relevance
“…Thus, it seems that a tight -CH 2 OCH 2 -tether outweighs this kinetic-energy propensity at TS 1 , which eventually leads to the (2+2) product. An analogous example was pointed out by us in the past in the context of 'rebound' hydroxylation vs dissociation in post H-atom abstraction reactivity, 27 where a reaction poised for dissociation in terms of KED follows the hydroxylation channel due to tethering. Such examples demonstrate the possibility to tilt the selectivity against the kinetic energy distribution at TS 1 .…”
Section: Comparison Of Rmcf With Existing Approaches Designed For Product Ratio Evaluationmentioning
confidence: 56%
See 2 more Smart Citations
“…Thus, it seems that a tight -CH 2 OCH 2 -tether outweighs this kinetic-energy propensity at TS 1 , which eventually leads to the (2+2) product. An analogous example was pointed out by us in the past in the context of 'rebound' hydroxylation vs dissociation in post H-atom abstraction reactivity, 27 where a reaction poised for dissociation in terms of KED follows the hydroxylation channel due to tethering. Such examples demonstrate the possibility to tilt the selectivity against the kinetic energy distribution at TS 1 .…”
Section: Comparison Of Rmcf With Existing Approaches Designed For Product Ratio Evaluationmentioning
confidence: 56%
“…Regarding the presence of shallow intermediates in branching PES and their influence on selectivity, we demonstrated in the past the successful application of the RMCF methodology to the rebound vs. dissociation dichotomous mechanism in C–H activation reactions by iron-oxo species. 27 In this context, a nascent carbon-centered radical can either (1) dissociate out of the solvent cage and become susceptible to trapping and further transformations, or (2) ‘ballistically’ recombine with the Fe–OH species in a nonequilibrium process. The kinetic energy distributions calculated using the RMCF protocol provided a clear and predictive rationalization of the selectivity observed in such cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Beyond the rebound step, instead, the substrate radical may escape from the cage and go through the dissociation mechanism. 49,50 The non-rebound pathway has been observed in some non-haem Fe IV O complexes, such as [N 4 PyFe IV (O)] 2+ and [(Bn-TPEN)-Fe IV O] 2+ . 18,25 Based on experimental and theoretical studies, the dissociation of the substrate radical has been shown to be feasible.…”
Section: Post H-atom Abstractionmentioning
confidence: 99%
“…As demonstrated in Refs. [37][38][39][40][41][42][43][44], H-atom-abstraction (HAA) reactivity and selectivity are strongly influenced by the interplay of redox and acidobasic components of the HAA thermodynamic force, which are usually inter-dependent so that a lower E°is compensated to some extent by a higher pK a and vice versa. Thus, to probe the 5'-dAdo * properties relevant for enzymatic HAA reactivity, we first analyze electrochemical behavior of 5'-dAdo * in aqueous solution and then we compare it with its behavior in models of the [Fe 4…”
Section: Redox and Acidobasic Properties Of The 5'-deoxyadenosyl Radimentioning
confidence: 99%